Direct observation of microstructures on superconducting single crystals of KxFe2−ySe2. (5th January 2017) - Tanaka, Masashi; Takeya, Hiroyuki; Takano, Yoshihiko
Abstract: Potassium-intercalated FeSe has been reported as a superconductor with a superconducting transition temperature ( T c ) of 30–48 K. However, the relationship among the surface morphology, compositional ratio, and crystal structure has not yet been clarified. This report directly reveals the correspondence among these three characteristics in single crystals with a T c onset of around 44 K by using a microsampling technique. Island-like parts on the surface of the crystals clearly exhibit the K x Fe2 Se2 structure with perfect FeSe layers, which is formed in conjunction with the K2 Fe4 Se5 phase. This results in the appearance of the T c onset at 44 K.